Proceedings Of The 19th Annual Meeting Of The Asia Oceania Geosciences Society (Aogs 2022) Singapore, 01 - 05 August 2022 - Liong, Shie-Yui; Satoh, Masaki (World Scientific Publishing Company, 2023)
The 19th Annual Meeting of the Asia Oceania Geosciences Society (AOGS 2022) was held from 1st to 5th August 2022. This proceedings volume includes selected extended abstracts from a challenging array of presentations at this conference. The AOGS Annual Meeting is a leading venue for professional interaction among researchers and practitioners, covering diverse disciplines of geosciences.